Rapamycin maintains the primordial follicle pool and protects ovarian reserve against cyclophosphamide-induced damage - Xiuying CHEN; Zhijing TANG; Haiyun GUAN; Hexia XIA; Chao GU; Yan XU; Bin LI; Wei ZHANG (The Society for Reproduction and Development, 2022)
Any abnormal activation of primordial follicles and subsequent depletion can irreversibly diminish the ovarian reserve, which is one of the major chemotherapy-induced adverse effects in young patients with cancer. Herein, we investigated the effects of rapamycin on the activation and development of ovarian follicles to evaluate its fertility-sparing therapeutic value in a cyclophosphamide (CTX)-treated mouse model. Based on ovarian histomorphological changes and follicle counting in 50 SPF female C57BL/6 mice, daily administration of 5 mg/kg rapamycin for 30 days was deemed an ideal dosage and duration for administration in subsequent experiments. Compared with the control group, rapamycin treatment inhibited the activation of quiescent primordial follicles, with no obvious side effects observed. Finally, 48 mice were randomly divided into four groups: control, rapamycin-treated, cyclophosphamide-treated, and rapamycin intervention. Body weight, ovarian histomorphological changes, number of primordial follicles, DDX4/MVH expression, apoptosis of follicular cells, and expression of apoptosis protease-activating factor (APAF)-1, cleaved caspase 3, and caspase 3 were monitored. Co-administration of rapamycin reduced primordial follicle loss and the development of follicular cell apoptosis, thereby rescuing the ovarian reserve after CTX treatment. On analyzing the mTOR signaling pathway, we observed that rapamycin significantly decreased CTX-mediated overactivation of mTOR and its downstream molecules. These findings suggest that rapamycin exhibits potential as an ovarian-protective agent that could maintain the ovarian primordial follicle pool and preserve fertility in young female patients with cancer undergoing chemotherapy.